Un roman de la rumeur médiatique. Événement, suspense et anticipation dans Le Péril bleu de Maurice Renard - Valérie Stiénon (ReS Futurae)
Maurice Renard’s Le Péril bleu tells the story of people who were abducted by invisible aliens. The suspense generated by the progressive revelation of these facts, whose horrifying dimension is growing, is punctuated by press announcements, expressions of social rumor and modulations of public opinion, while the official investigation only finds fake news. By showing how a media event is created with its sensational dimension, the novel develops some reflection and provides humor about testimony protocols. The article intends to study the “narrative tension” of the fiction, on the one hand by examining the generic frame of the futuristic novel, close to the form of the popular chronicle, on the other hand by comparing the book version of the story with its issue in L’Intransigeant in 1919.